Trypanosoma cruzi in the anal glands of urban opossums: I- isolation and experimental infections - S Urdaneta-Morales; I Nironi (Memorias do Instituto Oswaldo Cruz, 1996)
Opossums (Didelphis marsupialis) captured in intensely urbanized areas of the city of Caracas, Venezuela, were found infected with Trypanosoma cruzi. The developmental cycle of trypomastigote-epimastigote-metacyclic infective trypomastigote, usually occurring in the intestine of the triatomine vector, was taking place in the anal odoriferous glands of the opossums. Material from the glands, inoculated in young, healthy opossums and white mice by different routes, subcutaneously, intraperitoneally, orally, and into the eye, induced T. cruzi infections in all animals. Parasitemia, invasion of cardiac and skeletal muscle, and intracellular multiplication of amastigotes were observed. Inoculation of metacyclics from anal glands, cultured in LIT medium, gave equivalent results. All opossums survived; all mice died. Excreta of opossums may thus transmit Chagas' disease by contamination, even in urban areas where insect vectors are not present.